A Rademacher Type Formula for Partitions and Overpartitions - Andrew V. Sills (International Journal of Mathematics and Mathematical Sciences)
A Rademacher-type convergent series formula which generalizes the Hardy-Ramanujan-Rademacher formula for the number of partitions of 𝑛 and the Zuckerman formula for the Fourier coefficients of 𝜗4(0∣𝜏)−1 is presented.